Pumps as Turbines Fundamentals and Applications - Carravetta, Armando (Springer Tracts in Mechanical Engineering,, 2018)
This book provides users, pump manufactures, engineers, researchers and students with extensive information about pump's behavior in reverse operation. It reports on cutting-edge methods for selecting the proper PAT and improving PAT's efficiency, discusses PAT's reliability, economic issues and environmental impact as well. The book describes in detail electromechanical equipment of PAT systems, their installation and operation, and gives important practical insight into the use of PAT in water transmission and distribution systems, as part of thermal power plants and cooling systems, in oil distribution systems and other systems as well. It reports on different types on PAT control modes as well as on numerical methods useful for PAT analysis and implementation. All in all, the book represents a comprehensive practice-oriented reference-guide to design engineers, as well as PAT general users and manufactures. It also provides researchers with extensive technical information on the use of PAT thus fostering new discussions and ideas to improve current methods and cope with future challenges.